Elevated IL-6, IL-10, and IFN-γ levels in fatal elephant endotheliotropic herpesvirus – hemorrhagic disease cases suggest an excessive proinflammatory cytokine response contributes to pathogenesis - Hoornweg, Tabitha E.; Schaftenaar, Willem; IJzer, Jooske; Mulder, Myrna M. P.; Lugtenburg, Mariska; van Beest, Anne; de Haan, Cornelis A. M.; Rutten, Victor P. M. G. (Frontiers in Immunology, 2025)
IntroductionHemorrhagic disease developed as a consequence of an EEHV infection (EEHV-HD) is the leading cause of death of young Asian elephants in Zoos worldwide and also affects elephants in range countries. Although a cytokine storm has long been suggested to underlie disease pathogenesis, there is little evidence and the role of cytokines in EEHV-HD pathogenesis remains unclear to date.MethodsIn the current study, we compared mRNA levels of eight different cytokines between blood and tissue samples of EEHV-HD cases (n=11) and controls (n=12) in order to determine whether cytokines may contribute to EEHV-HD pathogenesis.ResultsWe show the presence of significantly elevated mRNA levels of IFN-γ, IL-6 and IL-10, cytokines typically associated with cytokine storms, in blood or tissues with high viral loads (heart and liver) of EEHV-HD cases. Comparable cytokine inductions were not observed in tissues with lower viral loads (tongue, lung and kidney), indicating an association between viral replication and cytokine induction, and suggesting damage observed in these tissues is likely collateral.DiscussionIn conjunction with pathological findings, including acute systemic inflammation and multiple organ dysfunction, we propose that a pathogen-induced cytokine storm indeed underlies EEHV-HD pathogenesis, which would support investigation into the use of anti-inflammatory therapies to control disease.